The Suppression Effect of Kebar Extract on Endometriosis Lesion MDA and TNF -a Independent to VEGF A Study in Endometriosis Mice Mode: Efek Supresi Ekstrak Kebar terhadap Lesi Endometriosis, MDA dan TNF-a, tidak Bergantung pada VEGF: Studi pada Model Tikus Endometriosis - Yuli Trisetiyono; Noor Pramono; Syarief T. Hidayat; Widjiati Widjiati (Indonesian Journal of Obstetrics and Gynecology, 2020)
Background: The pathogenesis of endometriosis remains unclear, and involves multifactorial etiologies. The increase in oxidative stress is known to be associated with this disease. Oxidative stress increases angiogenesis and supports the proliferation of endometriosis tissue in the peritoneal cavity. Kebar grass, a medicinal plant, is expected to increase antioxidant defense resulting in decreased oxidative stress, inflammation, angiogenesis, and reduced endometrial tissue implants. Objective: To investigate the effects of Kebar grass extract administration to MDA serum levels, TNF-a and VEGF expression, and the extension of the endometriotic lesions in mice model. Methods: This study was experimentally designed. It was conducted in the Department of Obstetrics Gynecology, Faculty of Medicine Diponegoro, University and Faculty of Veterinary Medicine, Airlangga University. Twenty-one mice were divided into three groups: the first group is control of 7 untreated endometriosis mice model, the second group consisted of 7 mice injected with leuprolide acetate 1mg/kgBB single dose, and the last group consisted of 7 mice fed with Kebar grass extract 3mg/day for 14 days. MDA serum level was measured by spectrophotometry, TNF-a and VEGF expression by IHC using Rammele Scale Index (ImmunoReactive Score), whereas the extension of the endometriotic lesions was measured using computerize tracing. Results: Both Kebar grass extract and leuprolide acetate administration significantly decrease MDA serum levels in endometriosis mice model, compare with the control group, (0.09±0.02 nmol, 0.11±0.07 nmol, and 0.30±0.06 nmol, respectively; p=0.001). TNF-α expression of the group treated with Kebar grass extract was lower than leuprolide acetate and control group (2.43±1.521 %, 4.86±0.458 %, and 7.26±2.898 %, respectively; p=0.002). However, there was no significant difference in VEGF expression among study groups (4.34±2.40 %, 5.11±1.95 %, and 7.40±3.49 % respectively; p=0.116). Finally, the extension of the endometriotic lesions of the mouse models administered with Kebar grass extract and leuprolide acetate was smaller than the control group (0 mm2, 4.54±7.75 mm2, and 34.80±13.09 mm2 respectively; p=0.005). Conclusion: Kebar grass extract has the effect of decreasing MDA serum levels and reducing TNF-α expression, resulted in smaller endometriotic lesions in mice, even though it does not affect VEGF expression. Keywords: malondialdehyde, tumour necrosis factor alpha, vascular endothelial growth factor, endometriotic lesion, kebar grass extract, endometriosis mouse